THE IDEA OF ANTI-CORRUPTION EDUCATION AS IT RELATES TO ISLAMIC EDUCATION IN INDONESIA - Aprillio Poppy Belladonna (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Corruption is still a national problem. Education is believed to be an alternative in eradicating corruption in Indonesia. For this reason, it is necessary to examine the views of Islamic education in overcoming corruption. This research aims to describe the concept of anti-corruption education from the perspective of Islamic education in Indonesia. This type of research is qualitative with a library study method, taken from credible sources in the form of relevant scientific data, including Google Scholar, Garuda, DOAJ, and SINTA. To test the validity of the data, the researcher checked the research data source. The results of this research conclude that the implementation of anti-corruption education is interpreted as: first, an effort to educate the generation (students) in developing a firm attitude to reject every act of corruption, collusion and nepotism. Second, reinforce students' views that corrupt acts are bad acts (not something ordinary or normal). Third, internalize values in students, including honesty, independence, discipline, responsibility, hard work, simplicity, courage and fairness.